Structure and characteristics of composite carbon-ceramic coatings for cathodes of contemporary chemical current sources - Pinchuk, Sofia; Levko, Elena; Domanskiy, Ievgen (Publishing House of Lviv Polytechnic National University, 2015)
The paper established the relationship between structure and properties of single-layered and multiple-layered composite carbon-ceramic coatings on the basis of lithium-manganese spinel on an aluminum substrate, allowing to optimize the structure of new cathode materials, which is promising for application in chemical current sources. Electrochemical properties were investigated using voltammetry and galvanostatic cycling. Investigation defined the amount of matter that takes part in the electrochemical processes, ability to discharge large currents; and performance during prolonged cycling. В роботі встановлено взаємозв’язок між структурою та властивостями одношарових та багатошарових композитних вуглець-керамічних покриттів на основі літій-манганової шпінелі на алюмінієвій підкладці, що дало можливість оптимізувати структуру нових катодних матеріалів, перспективних для використання в хімічних джерелах струму. За допомогою вольтамперометрії та гальваностатичного циклування вивчені їх електрохімічні властивості, встановлена кількість речовини, що приймає участь в електрохімічних процесах, здатність до розряду великими струмами та працездатність при тривалому циклуванні.
Структура та властивості композитних вуглець-керамічних покриттів для катодів сучасних хімічних джерел струму
Keywords: cathode material; chemical current source; voltammetry; galvanostatic cycling; катодний матеріал; хімічне джерело струму; вольтамперне та гальваностатичне циклування